pAMβ1-Associated Mobilization of Proteinase Plasmids from Lactococcus lactis subsp. lactis UC317 and L. lactis subsp. cremoris UC205 - Hayes, Finbarr (1990)
A combination of plasmid curing and DNA-DNA hybridization data facilitated the identification of proteinase plasmids of 75 (pCI301) and 35 kilobases (pCI203) in the multi-plasmid-containing strains Lactococcus lactis subsp. lactis UC317 and L. lactis subsp. cremoris UC205, respectively. Both plasmids were transferred by conjugation to a plasmid-free background only after introduction of the conjugative streptococcal plasmid, pAMβ1. All Prt(+) transconjugants from matings involving either donor contained enlarged recombinant Prt plasmids. UC317-derived transconjugants were separable into different classes based on the presence of differently sized cointegrate plasmids and on segregation of the pCI301-derived Lac and Prt markers. All UC205-derived transconjugants harbored a single enlarged plasmid that was a cointegrate between pCI203 and pAMβ1. The identification of prt genes on pCI301 and pCI203 derivatives was achieved by a combination of restriction enzyme and hybridization analyses.